2021
DOI: 10.3389/fvets.2020.589126
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infectious Agents Causing Neonatal Calf Diarrhea on Two Large Dairy Farms in Yangxin County, Shandong Province, China

Abstract: Neonatal calf diarrhea (NCD) is one of the most serious health challenges facing the livestock industry and has caused substantial economic losses due to increased morbidity and mortality rates. The present study investigated the main infectious pathogens causing NCD among cattle in Yangxin County, China. Sixty-nine fecal samples were collected from diarrheic newborn cattle and tested for infectious agents, including bovine rotavirus, bovine coronavirus, Escherichia coli K99, Cryptosporidium parvum, and Giardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…Diarrhea in calves frequently occurs in newborns within the age of 1∼3 months, and several studies on calf diarrhea target less than 3 months of age (Björkman et al, 2003;Alfieri et al, 2006;Monney et al, 2018;Singh et al, 2020;Wei et al, 2021). Likewise, the results of this study showed that the proportion of diarrheic feces collected from calves less than 3 months old was 92.3% (n=2,063) of 2,234 samples with confirmed age.…”
Section: Because Diarrhea Is One Of the Most Common Diseasessupporting
confidence: 71%
“…Diarrhea in calves frequently occurs in newborns within the age of 1∼3 months, and several studies on calf diarrhea target less than 3 months of age (Björkman et al, 2003;Alfieri et al, 2006;Monney et al, 2018;Singh et al, 2020;Wei et al, 2021). Likewise, the results of this study showed that the proportion of diarrheic feces collected from calves less than 3 months old was 92.3% (n=2,063) of 2,234 samples with confirmed age.…”
Section: Because Diarrhea Is One Of the Most Common Diseasessupporting
confidence: 71%
“…The primary etiologic agents for CD in calves of this age are viral with some exceptions where protozoa such as cryptosporidia can be identified ( Ngeleka et al, 2019 ). While more than one type of pathogen is often isolated from these calves, viruses and protozoa were commonly identified ( Berber et al, 2021 , Wei et al 2021 ). Bacteria such as Salmonella sp have been reported, but are much less common ( Gow et al, 2005 , Ngeleka et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some people even stated that they use them always, and others used them about half of the time. The use of antibiotics to treat NCD might not be necessary: most cases of NCD are caused by viral and parasitic pathogens, with E. coli K99 being the third most prevalent infectious agent in NCD worldwide [ 48 , 49 , 50 ]. Therefore, blanket antibiotic treatment of NCD should be strongly discouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics should only be used in calves suffering from NCD that are also affected by Gram-negative septicemia, mainly caused by E. coli [ 19 , 21 ]. As mentioned previously, studies differentiating infectious agents responsible for NCD show that E. coli only affects a small proportion of calves, making it only the third most prevalent cause of NCD worldwide [ 48 , 49 ]. Aggravatingly, as already mentioned, there is a lack of well design studies to determine the most effective antibiotic treatment for Gram-negative septicemia in calves suffering from NCD.…”
Section: Discussionmentioning
confidence: 99%